Pest categorisation of Citrus leprosis viruses. (14th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of the Citrus leprosis viruses for the EU territory and identified five distinct viruses, Citrus leprosis virus C (CiLV‐C), Citrus leprosis virus C2 (CiLV‐C2), Hibiscus green spot virus 2 (HGSV‐2), the Citrus strain of Orchid fleck virus (OFV) and Citrus leprosis virus N sensu novo (CiLV‐N) as causing this severe disease, most significantly in sweet orange and mandarin. These viruses have in common that they do not cause systemic infections in their hosts and that they all are transmitted by Brevipalpus spp. mites (likely but not confirmed for HGSV‐2). Mites represent the most important means of virus spread, while plants for planting of Citrus are only considered of minor significance. These well characterised viruses occur in South and Central America. Leprosis is currently regulated in directive 2000/29 EC and, together with its associated viruses, has never been recorded in the EU. All five viruses have the potential to enter into, establish in and spread within the EU territory, with plants for planting of non‐regulated hosts, fruits of Citrus and hitch‐hiking of viruliferous mites identified as the most significant pathways. Given the severity of the leprosis disease, the introduction and spread of the various viruses would have negative consequences on the EU citrus industry, the magnitude of which is difficult to evaluate given the uncertainties affecting the Brevipalpus spp. vectors (identity, distribution, density, transmission specificity and efficiency). Overall, leprosis and its five associated viruses meet all the criteria evaluated by EFSA to qualify as Union quarantine pests, but do not fulfil those of being present in the EU or of plants for planting being the main spread mechanism to qualify as Union regulated non‐quarantine pests. The main uncertainties affecting this categorisation concern the Brevipalpus spp. mite vectors.